Tinjauan Fikih Muamalah Dalam Akad Gadai - Ahmad Syukron Ulinnuha; Fitri Kurniawati (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
In the form of debts and receivables, Islamic law allows the lender to request items of financial value as collateral for the loan given to the debt recipient to maintain the trust of the debtor in the debt recipient, or what is commonly referred to as a pawn. This research uses a literature study method. with data obtained from collecting journal articles, books, scientific works, and so on that have related problems. The data that has been obtained is then analyzed using descriptive analysis methods. The results of the research are that pawn contracts (rahn) are permitted in Islamic law (fiqh) and sharia economic law, if the contracts used do not contain usury, gharar and maisi. Instead, it uses rahn and ijarah contracts which are in accordance with sharia principles. Based on the legal review above, it can be said that pawning in Islam is permitted and not prohibited in Islam. The legal basis is found in the Al-Qur'an, Hadith and Ijma